Flexible snake-like robot driven by single actuator - Lim, Mong King (2008)
Objective of this project is to develop a modular and hyper redundant robto manipulator with novel features such as: a) single actuator for all the DOFs of the robot, b) modular structure, c) CAN-bus based distributed motion control architecture with 32-bit microcontroller and d) visual programming interface.